The Epidemiology of Urolithiasis in an Ethnically Diverse Population Living in The Same Area - Cook, James; Lamb, Benjamin W; Lettin, Joanna E; Graham, Stuart J (Urology Journal, 2016)
Purpose: Little is known about whether migrants retain the risk of urolithiasis seen in their indigenous populations. We sought to evaluate the risk of renal colic between different ethnic groups among a diverse population in London. Materials and Methods: Data on a cohort of 100 consecutive patients presenting to our emergency department with acute renal colic over a 6 month period was collected retrospectively. Data was extracted from electronic patient record review, trust data and the 2011 census. Risk ratios were calculated and comparisons between groups were made with Chi-Squared test using SPSS. Results: The odds of renal colic among Turkish (odds ratio (OR) 6.57, 95% confidence interval (CI) 3.31-13.04, P < .001), Bulgarian (OR 4.94, 95% CI 1.82-13.44, P = .001), Romanian (OR 4.53, 95% CI 2.10-9.77, P < .001), Indian (OR 2.42, 95% CI 1.17-4.98, P = .013) and Pakistani (OR 2.25, 95% CI 1.38-3.67, P = .001) patients were significantly higher than the population average. The odds of colic among Black-Caribbean (OR 0.27, 95% CI 0.07 - 1.07, P = .045), Black-African (OR 0.27, 95% CI 0.07-1.07, P = .046), White-British (OR 0.44, 95% CI 0.30 - 0.66, P < .001) patients were significantly lower than the general population. Conclusion: This study suggests that migrants from countries known to have higher incidence of urolithiasis tend to retain this increased risk once in London. Such ethnic groups may benefit from targeted intervention to reduce the incidence of stone disease. Further research is needed with greater numbers in a range of populations to confirm this hypothesis.